Sociocultural theory for academic literacy research involving argumentation in institutions of higher learning - Eybers, O. O.; Paulet, E. (South African Journal of Higher Education, 2022)
Researchers in the field of academic literacy, specifically those focused on the first-year level in universities, are often required to articulate the theoretical framework that informs their critical orientation. In this process, an indication of the researcher’s ontological view of the nature of academic literacy practices should also be declared. Ontologically, this study questions whether academic literacy constitutes a mechanistic technology or a socially emergent mode of arguing in higher education. This article reviews concepts and theories that warrant the second stance and a sociocultural paradigm of academic literacy research. A sociocultural explanatory framework incorporates human identities and cultures into analyses of the ways that humans employ language in universities. This framework accentuates the influences of social context and power relationships in the designation of acceptable modes of argumentation in the university. The results of the study indicate that theoretical discussions in academic literacy research are epistemic and ontological in nature. Theoretical frameworks are epistemic constructs as they reflect a researcher’s conceptual understanding of the field of academic literacy. Conceptual paradigms are also ontological constructs due to their exposure of the researcher’s understanding of the nature of academic literacy practices as an element of human existence. The study concludes by articulating a seven-point ontology that researchers can apply towards theoretically framing their own studies in the field of academic literacy and argumentation.